OVERVIEW OF YOUNG WOMEN'S KNOWLEDGE ABOUT ANEMIA AND THE BENEFITS OF CONSUMING FE TABLETS IN THE WORKING AREA OF THE WABOROBO HEALTH CENTER - Rosna, Rosna (Institut Kesehatan dan Teknologi Buton Raya, 2024)
Anemia is a condition when hemoglobin, erythrocyte and hematocrit levels are below normal limits so that they cannot carry out their function as oxygen providers for body tissues. The purpose of the study was to find out the picture of adolescent girls' knowledge about anemia and the benefits of consuming Fe tablets in the Working Area of the Waborobo Health Center in Baubau City for the period from March to August 2023. This study used a descriptive research design, with a cross sectional study design. The total sample pollutation is 45 samples where the side taking technique is total sampling. The research instrument used to collect data was a questionnaire of 20 questions consisting of positive and negative questions. The results showed that most young women in the Waborobo health center area had sufficient knowledge, namely as much as 40%, good knowledge as much as 22% and those with less knowledge as much as 37.8%. Based on the results of the study, there is still a need to improve counseling and education services in schools through health counseling by health workers to provide minimal information that includes basic knowledge of anemia and the benefits of consuming Fe tablets that are carried out continuously can increase the knowledge of adolescent girls.